Factors Affecting the Formation and Development of Human Capital - Asamkhodjaeva Shoira (Peerian Journals Publishing, 2023)
The essence of investing in human capital and factors affecting the formation and development of human capital, as well as their composition, are studied in the article. One of the main factors is the development of human capital through the education system
Keywords: human capital; intellectual capital; investment; education